Minerals Composition and Characterization of the Hatchery Eggshell Waste Treated with Different Preparation Methods (Faculty of Animal Science Universitas Brawijaya, 2021)
The preparation process needs to be carried out in the treatment of hatchery waste. The objective of the study was to determine the mineral content and characterization of the eggshell waste after preparation. An experiment was arranged on a completely randomized design (CRD). Preparation treatment consisted of; T1: shell waste watered with distilled water; T2: shell waste soaked in distilled water for 12 h; T3: shell waste soaked in 0.5% NaOH for 720 min; and T4: shell waste boiled at 80°C for 15 min and soaked in 5% H3PO4 for 15 min. The data were analyzed using Analysis of Variance (ANOVA), and if any differences, a Duncan Multiple Range Test (DMRT) post hoc tests were carried out. Composition of proximate and mineral were detected by using X-Ray Fluorescence (XRF). Results indicated that proximate analysis of the dry matter content were T4: 98.98±0.01; T3: 98.58±0.04; T2: 98.75±0.08; and T1: 98.72±0.03. The calcium content of the treatment from the highest was T3: 24.22±0.31; T1: 22.80±0.57; T2: 22.77±0.71; and T4: 21.55±0.46. It may be inferred that the treatment technique had no major impact on the eggshells physical characteristics. However, boiling treatment at 80°C for 15 min and soaking in 5% H3PO4 reduced the eggshell waste's Mg, Si, and Ca content. The addition of 0.5% NaOH immersion did not degrade Mg, Ca, and Si of eggshell waste.